2016
DOI: 10.1016/j.jnucmat.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

W nano-fuzzes: A metastable state formed due to large-flux He+ irradiation at an elevated temperature

Abstract: W nano-fuzzes have been formed due to the large-flux and low-energy (200eV) He + irradiation at W surface temperature of 1480°C. Microscopic evolution of W nano-fuzzes during annealing or low-energy (200eV) He + bombardments has been observed using scanning electron microscopy and thermal desorption spectroscopy. Our measurements show that both annealing and He + bombardments can significantly alter the structure of W nano-fuzzes. W nano-fuzzes are thermally unstable due to the He release during annealing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This trend of reversible flow was confirmed by annealing of the fuzzy W surface to a high temperature in absence of Helium irradiation. Hence, obvious reduction in the W-fuzz height was reported [48][49][50].…”
Section: B Effect Of He + Ion Fluxmentioning
confidence: 99%
“…This trend of reversible flow was confirmed by annealing of the fuzzy W surface to a high temperature in absence of Helium irradiation. Hence, obvious reduction in the W-fuzz height was reported [48][49][50].…”
Section: B Effect Of He + Ion Fluxmentioning
confidence: 99%
“…The observed incubation fluence (the minimum fluence before fuzz growth) is required for bubbles to form [21] which are required for fuzz growth [22]. At high temperatures, due to the low thermal conductivity of the fuzz [7,23], tendrils heat up and reintegrate back into the bulk. Irradiation by impurities or high-energy He ions (> 120 eV) can lead to sputtering, the emission of W atoms from the sample, which erodes surface features [24].…”
Section: Conditionsmentioning
confidence: 99%
“…In a thick sample (relevant to fusion reactors), He bubbles are required for fuzz initiation; this could be to drive adatom diffusion. Finally, annealing fuzz [23] leads to He release and subsequent destruction of the fuzz nanostructure; without the stresses from He bubbles, the metastable fuzz disappears when heated. Fiflis et al [30] replaced He + ions with Ne + which did not lead to fuzz.…”
Section: Adatom Diffusionmentioning
confidence: 99%
“…However, their accumulation in the subsurface region alters the material properties and surface morphology, significantly degrading the beneficial properties of tungsten. Numerous studies [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] have demonstrated that a tungsten surface with surface temperature T s 1000 K, when exposed to a high flux of low-energy He + ions ( 20 eV) and fluences Φ 10 24 He/m 2 in linear plasma devices and tokamak plasmas, forms fine fiber-like nanostructures, often referred to as 'fuzz'. The thickness of the fuzz layer has been observed to increase as the square root of helium fluence after a delayed onset (incubation fluence) [25].…”
Section: Introductionmentioning
confidence: 99%
“…The fuzz layer can grow to thicknesses of a few micrometers, degrading the mechanical and thermal properties of exposed tungsten [26]. Furthermore, fuzz is fragile, thermally unstable, and can easily be sputtered [21,22]. Therefore, during sudden stress or high-heat loading, it can easily detach [27,28], forming dust that can cool the plasma, thereby adversely affecting the stability of the fusion plasma.…”
Section: Introductionmentioning
confidence: 99%